Studying Characteristics of Traction Induction Motors for Variable-Speed Mine Electric Locomotive; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Baranov P. R. Pavel Rudolfovich; Kladiev S. N. Sergey Nikolaevich; Borisov S. V.; Philipas A. A. Alexander Alexandrovich (Designing and Modelling of Machines and Mechanisms, 2015)
Title screen